101 of Surgical Instruments Naming, Recognizing, Handling and Presenting - Liehn, Margret; Schlautmann, Hannelore; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
Compact practical knowledge: an overview of surgical instruments This book offers all specialists in the operating room a compact overview of the most important surgical instruments and their handling.Regardless of whether you are already experienced in the OR or the area is new to you: Here you will learn to recognize surgical instruments better and to use them safely. Benefit from the experienced authors and master your day-to-day work with confidence. A specialist book for all OR specialists that helps you familiarize yourself with new employees, provides suggestions for specialist training or to look up questions about the instruments. This book is a translation of the original German 3rd edition 1x1 der chirurgischen Instrumente by Margret Liehn, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2017. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The content: Basics, material science, surface properties 200 illustrations to help you distinguish between instruments Use and handling of surgical instruments Reprocessing and maintenance of instruments The authors: Margret Liehn, specialist nurse in the surgical service, lecturer for surgical care and surgical teaching. Hannelore Schlautmann, specialist nurse in the surgical service.
Introduction: History of instrument manufacture, materials, standardization, surfaces, basic rules -- Surgical instruments -- Basic instruments -- Special instruments -- Table structure -- Handling -- Regulations for processing and disposal -- Literature.
Keywords: Nursing; Surgery; Nursing; Surgery; Surgical Instruments; General Surgery -- instrumentation